2018
DOI: 10.1053/j.ajkd.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

International Differences in the Location and Use of Arteriovenous Accesses Created for Hemodialysis: Results From the Dialysis Outcomes and Practice Patterns Study (DOPPS)

Abstract: Large international differences exist in AVF location, predictors of AVF location, successful use of AVFs, and time to first AVF/AVG use, challenging what constitutes best practice. The large US shift from lower- to upper-arm AVFs raises serious concerns about long-term health implications for some patients and how policies and practices aimed at increasing AVF use have affected AVF placement location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 22 publications
(25 reference statements)
7
124
2
4
Order By: Relevance
“…Finally, there are country differences in anatomic location of AV accesses. Upper arm accesses are now more common than forearm AVFs in the US , and are more likely to be placed in the lower arm in Japan . The reason this matters is that Japanese guidelines recommend that the flow rate of AVF should be maintained from 500 to 1000 mL/min , while European guidelines have somewhat higher values .…”
Section: Access To Transplant and Modality Usementioning
confidence: 99%
“…Finally, there are country differences in anatomic location of AV accesses. Upper arm accesses are now more common than forearm AVFs in the US , and are more likely to be placed in the lower arm in Japan . The reason this matters is that Japanese guidelines recommend that the flow rate of AVF should be maintained from 500 to 1000 mL/min , while European guidelines have somewhat higher values .…”
Section: Access To Transplant and Modality Usementioning
confidence: 99%
“…Indeed, there was a significant difference in patency rates between upper and forearm AV accesses, with 1-year patency of 74% versus 58%, respectively. This trend is echoed by others 18,[28][29][30][31] and has contributed in the shift from forearm to upper-arm AV accesses predominantly in the US 32 . Patients with previous failed AV access are susceptible to future AV access failure and this is conceivably related to the presence of pre-existing risk factors for failure or the occurrence of maladaptive vascular remodelling and neointimal hyperplasia following creation of the previous failed AV access 33 .Brachial-cephalic AV accesses had better patency rates compared to brachial-basilic and this is opposed to previous studies which have shown less primary failures for basilic vein AV accesses and similar cumulative access survival [34][35][36] .…”
Section: Discussionmentioning
confidence: 71%
“…However, no post-placement outcomes other than maturation were evaluated and the study did not include AVG placements. We found that AVG also required a median length of 53 days between access placement and first use for hemodialysis, which was longer than the Dialysis Outcomes and Practice Patterns Study reported median time to first use of 29 days, although the present cohort may contain more elderly patients which may account for a longer maturation time [20]. In our dataset, time to first use may be slightly skewed due to CROWNWeb reporting only once per month on any given day.…”
Section: Doi: 101159/000495355mentioning
confidence: 62%